2000
DOI: 10.1084/jem.191.10.1675
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Tumorigenicity in Breast Cancer Cells by the Microfilament Protein Profilin 1

Abstract: Differential display screening was used to reveal differential gene expression between the tumorigenic breast cancer cell line CAL51 and nontumorigenic microcell hybrids obtained after transfer of human chromosome 17 into CAL51. The human profilin 1 (PFN1) gene was found overexpressed in the microcell hybrid clones compared with the parental line, which displayed a low profilin 1 level. A comparison between several different tumorigenic breast cancer cell lines with nontumorigenic lines showed consistently low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
129
3

Year Published

2003
2003
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 129 publications
(151 citation statements)
references
References 35 publications
15
129
3
Order By: Relevance
“…Third, the present study is the first demonstration of the in vivo effect of Pfn1 overexpression on breast cancer cells in an orthotopic setting. Our finding that Pfn1 overexpression suppresses orthotopic tumorigenicity of MDA-MB-231 cells reproduces previous results reported for another breast cancer cell line in subcutaneous xenograft models (Janke et al, 2000;Wittenmayer et al, 2004), and thus provides a further supportive evidence for the tumour-suppressive property of Pfn1 in breast cancer.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Third, the present study is the first demonstration of the in vivo effect of Pfn1 overexpression on breast cancer cells in an orthotopic setting. Our finding that Pfn1 overexpression suppresses orthotopic tumorigenicity of MDA-MB-231 cells reproduces previous results reported for another breast cancer cell line in subcutaneous xenograft models (Janke et al, 2000;Wittenmayer et al, 2004), and thus provides a further supportive evidence for the tumour-suppressive property of Pfn1 in breast cancer.…”
Section: Discussionsupporting
confidence: 90%
“…Similar to previous observation of Pfn1 downregulation in human breast cancer tissue and a wide range of other breast carcinoma cell lines (Janke et al, 2000), we observed that MDA-MB-231, our model breast cancer cell line, also expresses significantly less Pfn1 compared to normal HMEC ( Figure 1A). Because of a general theme of Pfn1 downregulation in many different breast cancer cell lines, we specifically hypothesised that downregulation of Pfn1 expression confers increasing aggressiveness to both normal HMEC and breast cancer cells.…”
Section: Loss Of Pfn1 Expression Enhances Motility Of Breast Cancer Asupporting
confidence: 90%
See 3 more Smart Citations